Effects of cost information, environmental innovation, and gender on new product development performance - Pihany, Alvina Windy; Jatiningsih, Dyah Ekaari Sekar (Journal of Accounting and Investment, 2025)
Research aims: This study aims to examine the influence of cost information,environmental innovation practices, and gender on new product developmentperformance.Design/Methodology/Approach: Experimental methodology with 2x2 factorial design. There were 117 participants consisting of students from the Faculty of Economics and Business who had taken Management Accounting and Cost Management courses.Research findings: The findings indicate that the performance of new product development is not significantly impacted by cost information or environmental innovation techniques. Nonetheless, there are notable relationships between gender and environmental innovation methods and cost information, suggesting that the influence varies depending on the designer's gender. Theoretical contribution/ Originality: This study fills a gap in the literature by investigating the interaction between gender, environmental innovation strategies, and cost information in developing new products. The study adds to our understanding of how these factors could influence the efficacy of product development and decision-making pertaining to sustainability.Practitioner/Policy implication: This study suggests that firms need to considergender differences in environmental innovation practices to optimize newproduct development. In addition, presenting relevant cost informationremains important in supporting strategic decision-making.Research limitation/Implication: Unequal group sizes may reduce statistical sensitivity. Using students limits real-world relevance. Future studies should consider work experience and include professionals to enhance external validity.